ACCESSIBILITY AND INCLUSION IN THE FOOD MARKET: A Case Study on the Importance of Braille on Packaging - Fidelis, Matheus Henrique; Terazzi, Luis Fernando (Revista Interface Tecnológica, 2025)
This study aims to analyze the importance of social inclusion in the food market through the implementation of Braille on food product packaging, focusing on a major company in the food industry. The research adopts a qualitative approach, using the case study method, and is based on interviews with professionals from the Production, Quality, and Marketing departments. The results revealed that, although the company has not yet implemented Braille on its packaging, there is a growing awareness of its importance, both for social inclusion and corporate social responsibility. Furthermore, it was identified that implementing Braille can create a competitive advantage in the market and enhance the company's image among consumers who are increasingly aware of the need for accessibility. The research also highlighted challenges related to costs and the adaptation of production processes. The inclusion of Braille represents not only a measure of accessibility but also an opportunity for innovation and brand strengthening, contributing to the development of a more inclusive society.
Keywords: Equity; Social Inclusion; Responsibility